The digital transformation of the innovation process: orchestration mechanisms and future research directions. Issue 1 (2nd January 2022) - Urbinati, Andrea; Manelli, Luca; Frattini, Federico; Bogers, Marcel L. A. M.
ABSTRACT: The importance of digital innovation is widely acknowledged among managers and scholars alike. However, its actual conceptual treatment in academic research is not necessarily clear or precise. Most research considers digital innovation as the final result of adopting digital technologies, such as new products, processes, services, or business models. In other words, this research advances the concept of digital innovation as an outcome . In parallel to this research on digital innovation as an outcome, the concept of digital innovation as a process has emerged, linking innovation capabilities, organizational structures, boundaries, and technology management in organisations. The scattered existing research on digital innovation as a process explores the anatomy of the digital transformation of the innovation process by focusing on its phases, underlying mechanisms, barriers, and enabling factors. We argue that management research should pay more attention to this perspective on digital innovation. Therefore, in this essay, we take stock of research on the topic and identify four orchestration mechanisms that are inherently processual, enabling the firm to effectively coordinate and leverage different types of resources to create and capture value through the adoption and exploitation of digital technologies in the innovation process. Based on these orchestration mechanisms, we develop an agenda for future research that will hopefully inform further scholarly inquiry in the field of digital innovation.